Curious Travellers: New Journeys for the Home Tour - Mary-Ann Constantine (Humanities)
This short concluding chapter reflects on the work of an ongoing collaborative academic project focused on the C18th home tour. Curious Travellers could be described as a ‘crucible’ project—a space in which different media, different perspectives, and different research skills combine and collide. Currently funded by the AHRC, it is a digital humanities project involving TEI tagging and crowd-sourcing, but its foundation is archival research into manuscripts. It is focused through the influential Tours of Wales and Scotland published by the naturalist and antiquarian Thomas Pennant, yet it seeks to unpick the multiple voices and collaborations behind his texts and to explore their legacy in the journeys and texts of others. The creation of new editions continues to generate new topics and research questions, including Anglophone/Celtic-language interactions; the writings of women tourists; the role of material objects (specimens and souvenirs) and of visual culture in knowledge exchange and production. Increasingly, project researchers are relating their work to broader global contexts of colonialism and environmental history. The diversity of the genre has proved hugely stimulating for a range of audiences beyond academia: community engagement and creative practices have been a key feature from the start. There are, of course, challenges—practical, methodological, financial. This reflective piece will acknowledge the constraints, as well as the possibilities, of being multi-stranded, cross-disciplinary—and intermittently funded.